Propriedades estáticas e dinâmicas de portadores em heteroestruturas semicondutoras - Bittencourt, Antonio Carlos Rodrigues (2002)
We have studied the dynamic and the stationary properties of carriers in semiconductor heterostructures submitted to electric fields AC and DC and to magnetic fields within the eﬀective-mass approximation based on model multiband k · p. The method used to calculate the electronic structure uses the combination of techniques of finite differences and the inverse power method. As example to test the eﬃciency of the method, we have studied optical properties in multiple quantum wells of GaAs/AlGaAs containing a delta-doping nipi structure. We have calculated the single pair electron-hole energy recombination and we estimated critical temperatures where the interband optical transitions changes its character from indirect to direct. We have also calculated the electronic structure of holes in quantum wells of GaAs/Ga1−xAlxAs in the presence of longitudinal magnetic and electric parallel fields as initial part of the study of the magnetotunneling in double barrier. The resonant tunneling of the carriers in double barrier is investigated using the formalisms based on the scatterring-matrix and on the finite diﬀerence technique. The implicit method to simulate the time dependent transport properties is obtained in terms of Magnus expansion for the evolution operator by using a factorization based on the approach of Padé (M/M). This method has shown quite stable, besides allowing high order of precision. We have calculate the quasi-energy, medium displacement, transmission probability, AC Stark eﬀect and tunneling time of the carriers in a quantum well GaAs/Ga0,7Al0,3As submitted to an AC potential, both with k = 0 and k 6= 0. Our results have revealed that carriers present dynamics completely diﬀerent from each other depending strongly on the ratio between applied AC frequency ω and the carrier localization frequency ωl = (E ~ ). The AC Stark eﬀect has adiabatic type that is inserted into the initial conditions. The quasi-energy of all carriers, except the ligth-hole LH1 at k = 0, present a similar quasi-parabolic dependence with the intensity of the field β = (eF0Lz }ω ), as is observed in static cases. The degree of localization of the carriers is investigated through the calculation of tunneling times. In general, states show time localization induced by laser frequencies larger that ωl for many states with k = 0. For k > 0 the inherent mixture among the states of the valence band produces an increase in the transmission probability. The field tilted barrier of potential leads to quasi-energies near to the border of the QW, favoring the escape of carriers from quantum well region if compared to their time localization regimes.